THE MEANING OF PROFIT BASED ON COST–VOLUME PROFIT (CVP) IN THE MOTIAYO CULTURE: A CASE STUDY OF THE ROLAN UPIYA KARANJI MSME IN GORONTALO - Mustaqim R. Koem; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The purpose of this study is to understand the meaning of Cost Volume Profit (CVP)-based profit in the Motiayo culture of the Rolan Upiya Karanji Gorontalo MSME. The study uses a qualitative approach with a configurative ideographic case study method to explore the experiences and meanings of business actors in depth. Data collection techniques were carried out through in-depth interviews, observation, and documentation, while data analysis used thematic analysis. The results of the study indicate that the meaning of profit is not understood as maximizing profits, but rather as a social construction formed through the interaction between economic rationality and cultural values. There are two main meanings found, namely profit as a balance of stakeholder interests and profit as social legitimacy. Profit is interpreted as a balance of stakeholder interests when business actors balance cost management, production volume, and social relations within the business. In addition, profit is also interpreted as social legitimacy when business success is measured based on acceptance and sustainability of work relationships and the social environment. This study shows that the concept of Cost Volume Profit not only functions as an economic analysis tool but can also be understood in a social and cultural context. Thus, this research contributes to the development of accounting studies that are not solely financially oriented but also consider the social and cultural dimensions of business practices.